2018
DOI: 10.1111/afe.12303
|View full text |Cite
|
Sign up to set email alerts
|

Arthropod biodiversity in olive groves under two soil management systems: presence versus absence of herbaceous cover crop

Abstract: 1 Agricultural intensification has greatly affected biodiversity in recent decades. One common and recent transformation that has taken place in Mediterranean countries is olive grove intensification, although its effects on biodiversity have rarely been studied. 2 In the present study, we investigated the effect of soil management practices, with versus without soil cover crops, on the arthropod abundance, richness, diversity and species composition in Andalusia olive groves, South Spain. 3 The results obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 84 publications
0
37
0
Order By: Relevance
“…In the case of the SSP2, there is a positive impact on costs due to the availability of raw material for making compost based on pruning residues. With respect to the negative impacts on costs, the implementation of these practices represents an increase in the number of operations [66]. In the first case, it is due to the processing of pruning residues for their subsequent use.…”
Section: Principal Impacts Of Adopting Soil Sustainable Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the SSP2, there is a positive impact on costs due to the availability of raw material for making compost based on pruning residues. With respect to the negative impacts on costs, the implementation of these practices represents an increase in the number of operations [66]. In the first case, it is due to the processing of pruning residues for their subsequent use.…”
Section: Principal Impacts Of Adopting Soil Sustainable Practicesmentioning
confidence: 99%
“…This low level of organic matter in coarse textured soils such as those in our case, affects the structural stability of the aggregates which, in response to the impact of the raindrops or as a consequence of the mechanized tillage, tend to disintegrate on the surface, leading to a crusting of the upper surface which hinders the infiltration of new rainfall and increases the surface runoff and risk of erosion. The use of sown vegetal covers, specifically selected for these soil and climate conditions in periods of lower water deficit, along with spontaneous herbaceous cover, contribute to protecting the soil against the direct impact of the raindrops, slowing down the surface runoff and improving infiltration through its root system, contributing to increasing the value of the effective rain [63], and stabilizing the macroaggregates of the soil as a direct consequence of its root system and indirectly fostering the development of mycorrhizal fungi [64]; the biological diversity increases on both a plot scale and in the soil itself and the nutrient balance is modified [65,66]; its incorporation in the soil will have a temporary effect on the total organic carbon content due to the labile nature of the material incorporated, but it will affect the balance of the soil organic carbon fractions, which have a high ecosystem value [67]. The contribution of sown covers is due to the need to increase biomass contributions over those made by spontaneous vegetation, which is not sufficient in itself.…”
mentioning
confidence: 99%
“…A high percentage of studies found lower pest pressure in complex landscapes (Bianchi et al ., 2006) and particularly in olive grove agroecosystems, B. oleae captures at short distances were related to several complexity parameters (Ortega and Pascual, 2014). Also, soil cover crops strongly improved the diversity of arthropods in olive groves, along with variables such as the diversity of the plant community and Shannon index of the landscape (Carpio et al ., 2019). In contrast, in a meta-analysis, natural enemies were positively related with landscape complexity but pest abundances did not show a significant response (Chaplin-Kramer et al ., 2011), highlighting the need of further research with different organisms and agroecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, one of the most effective measures by which to reduce soil erosion is the use of cover crops [10][11][12], a practice that has been promoted through subsidies and cross compliance from the CAP [13]. The use of cover crops in the lanes of olive groves has been shown to have a beneficial environmental impact on experimental orchards by reducing soil erosion [14,15] and increasing biodiversity [16][17][18]. However, the establishment of cover crops in commercial olive orchards raises various agro-economic and practical issues, especially in rain-fed orchards, owing to the competition between olive trees and cover crops for soil water.…”
Section: Introductionmentioning
confidence: 99%